2010
DOI: 10.1536/ihj.51.30
|View full text |Cite
|
Sign up to set email alerts
|

High Homocysteine Levels Predict the Recurrence of Atrial Fibrillation After Successful Electrical Cardioversion

Abstract: SummaryRecent data suggest that elevated plasma levels of homocysteine could be associated with atrial fibrillation (AF). The aim of our study was to investigate whether elevated plasma Hcy levels were predictive of the recurrence rate of AF after successful electrical cardioversion.Eighty-three patients (63 ± 12 years, 61.4% men) with persistent AF lasting at least 7 days were included after successful electrical cardioversion. Echocardiography and plasma homocysteine assay were performed prior to cardioversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
13
1
Order By: Relevance
“…Regarding AF specifically, elevated plasma total homocysteine, a metabolite closely related to the choline oxidation pathway, has been associated with increased risk of AF recurrence following electrical cardioversion 33. In the Framingham Heart Study,12 no significant association between plasma betaine and risk of incident AF was reported, with age‐ and sex‐adjusted HR (95% CI) 1.03 (0.87‐1.22).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding AF specifically, elevated plasma total homocysteine, a metabolite closely related to the choline oxidation pathway, has been associated with increased risk of AF recurrence following electrical cardioversion 33. In the Framingham Heart Study,12 no significant association between plasma betaine and risk of incident AF was reported, with age‐ and sex‐adjusted HR (95% CI) 1.03 (0.87‐1.22).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the extracellular matrix resulting from an imbalance between MMPs and their TIMPs can lead to atrial structural remodeling, thereby creating a nidus for AF development and propagation [48]. Homocysteine, an important mediator of MMP activity, can serve as a predictor of AF recurrence [49]. In a recent prospectively conducted study [50], in patients with essential HTN and normal LVEF, those with AF had higher levels of MMP and lower levels of TIMP compared to patients with sinus rhythm.…”
Section: Biomarkers In Atrial Fibrillationmentioning
confidence: 99%
“…Duyuler et al found an independent relationship among the iron status, Tp-e interval and Tp-e/QT ratios of elite sport players that were also not correlated with serum homocysteine levels [33]. Previous researchers also found that the homocysteine levels determined prior to electrical cardioversion could predict recurrence of AF after successful restoration of sinus rhythms [34]. However, few studies focused on the QTc interval.…”
Section: Discussionmentioning
confidence: 99%